Supragingival biofilm control and systemic inflammation in patients with type 2 diabetes mellitus - Hilana Paula Carillo ARTESE; Priscila Larcher LONGO; Giovane Hisse GOMES; Marcia Pinto Alves MAYER; Giuseppe Alexandre ROMITO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this study was to evaluate the effect of strict supragingival biofilm control on serum inflammatory markers and on periodontal clinical parameters in type 2 diabetes mellitus (T2DM) patients with chronic severe periodontitis. Twenty-four individuals with T2DM and periodontitis were randomly allocated to two treatment groups. The supragingival therapy group (ST, n = 12) received supragingival scaling, whereas the intensive therapy group (IT, n = 12) underwent supra- and subgingival scaling, as well as root planing. Patients from both groups received professional oral hygiene instructions every month. Data regarding visible plaque index (VPI), gingival bleeding index (GBI), bleeding on probing (BOP), probing pocket depth (PPD), clinical attachment level (CAL), serum levels of interleukin (IL)-6, IL-17A, IL-8, tumor necrosis factor α (TNF-α), monocyte chemoattractant protein (MCP)-1 enzyme-linked immunosorbent assay (ELISA), and glycated hemoglobin (HbA1c) levels were obtained at baseline and at 6 months post-therapy. Both therapies resulted in the improvement of almost all clinical periodontal parameters (p < 0.05). There were no differences in TNF-α, IL-8, IL-17A and HbA1c levels in either group (p >0.05), between the two periods. However, MCP-1 levels were significantly reduced in both the ST (p = 0.034) and the IT (p = 0.016) groups, whereas the serum IL-6 levels were significantly reduced only in the IT group (p = 0.001). Strict control of supragingival biofilm has a limited effect on systemic inflammatory markers, and a moderate effect on periodontal clinical parameters.